Effect of Whey Protein Isolate-Meniran Extract (Phyllantus niruri L.,) Eencapsulation Using Casein Hydrolysate on Foam, Optical Microscopy, Particle Size, and Viscosity - Lukman Hakim; Nicolays Jambang (Faculty of Animal Science Universitas Brawijaya, 2023)
The purpose of this study was to determine the effect of whey protein isolate (WPI)-extract of meniran (Phyllanthus niruri L.) encapsulation using casein hydrolyzate on foam overrun, optical microscopy, particle size and viscosity. The materials used was whey protein isolate, an extract of meniran (Phyllanthus niruri L.) encapsulated using casein hydrolyzate. The method used was a completely randomized design (CRD) with 5 treatments of casein hydrolyzed as encapsulation material, 0%, 2%, 4%, 6% and 8%, namely P0, P1, P2, P3 and P4 repectively, with 3 replications. The variables observed were foam overrun, particle size, and viscosity which were analyzed using analysis of variances (ANOVA). If there is a significant or very significant difference, analysis will be continued with the DMRT (Duncan Multiple Range Test). Variable of optical microscopy was analyzed descriptively. The results showed that whey protein isolate-meniran extract encapsulation using casein hydrolyzate gave a very significant difference (P<0.01) on in viscosity and foam overrun but did not give significant difference (P>0.05) on particle size. The average foam overrun value was 325% - 400%, the viscosity was 0.985 cP - 1.015 cP, the particle size was 0.8944 nm - 1.5031 nm, and optical microscopy showed that the most abundant distribution and amount of foam was observed in P4, namely whey protein isolate-meniran extract encapsulated with 8% casein hydrolyzate. Along with the addition of casein hydrolyzate with different concentrations (2%, 4%, 6%, 8%), the distribution and shape of the foam became more even and uniform. The conclusion of this study was that the addition of 6% casein hydrolyzate on the encapsulation effect of whey protein isolate-meniran extract was able to maintain the physical properties of WPI-meniran extract on viscosity, optimal particle size, foam overrun, and optical microscopy with a shape, uniform foam distribution and lamella tend to be thick.